2010
DOI: 10.1017/s0024282910000551
|View full text |Cite
|
Sign up to set email alerts
|

Lecanora microloba, a new saxicolous species from Poland

Abstract: A new lichenized fungus, Lecanora microloba Ś liwa & Flakus, is described from the subnival belt of the Polish Tatra Mountains. It is characterized by small, saxicolous thalli with minutely lobulate marginal areoles and mostly broadly sessile and constantly pale coloured apothecia that are grouped predominantly in the centre of the thallus. Anatomically the species is distinguished by coarse granules in the epithecium which are distinctly bright in polarized light. The species contains gyrophoric and usnic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 16 publications
0
10
0
9
Order By: Relevance
“…Although recent detailed taxonomic studies have revealed new species (e.g. Śliwa & Flakus, ; Eberhardt et al ., ) (Fig. G, H), their distribution and status need verification.…”
Section: The Carpathians As a Biodiversity Hotspotmentioning
confidence: 89%
“…Although recent detailed taxonomic studies have revealed new species (e.g. Śliwa & Flakus, ; Eberhardt et al ., ) (Fig. G, H), their distribution and status need verification.…”
Section: The Carpathians As a Biodiversity Hotspotmentioning
confidence: 89%
“…2001;Czarnota & Coppins 2006Czarnota 2007;Krzewicka i in. 2009;Śliwa & Flakus 2011) i liczne doniesienia o odnalezieniu kolejnych nowych stanowisk rzadkich gatunków (np. Flakus 2004;Flakus & Bielczyk 2006;Kościelniak & Kiszka 2007;Kościelniak 2008;Czarnota & Kukwa 2007Wilk 2011;Śliwa & Krzewicka 2012;Czarnota 2016;Matura 2016;Śliwa & Matura 2018).…”
Section: Wstępunclassified
“…The study revealed numerous interesting lichenized and lichenicolous fungi from the mountain range (Flakus 2007;Kukwa & Flakus 2009), as well as a new species (Ś liwa & Flakus 2011). The study revealed numerous interesting lichenized and lichenicolous fungi from the mountain range (Flakus 2007;Kukwa & Flakus 2009), as well as a new species (Ś liwa & Flakus 2011).…”
mentioning
confidence: 92%
“…A survey of the lichens of the subnival belt in the Tatra Mountains of Poland, conducted by the first author between 2003 and 2006, indicated this area to be an important biodiversity hot-spot in the Carpathians. The study revealed numerous interesting lichenized and lichenicolous fungi from the mountain range (Flakus 2007; Kukwa & Flakus 2009), as well as a new species (Śliwa & Flakus 2011). Along with other valuable collections, a member of the L. varia group was found that matched in all characters the recently described L. printzenii .…”
mentioning
confidence: 99%